Prognostic Value of the Tumour-Infiltrating Dendritic Cells in Colorectal Cancer: A Systematic Review. (2nd January 2015) - Malietzis, George; Lee, Gui H.; Jenkins, John T.; Bernardo, David; Moorghen, Morgan; Knight, Stella C.; Al-Hassi, Hafid O.
Abstract: Dendritic cells (DCs) either boost the immune system (enhancing immunity) or dampen it (leading to tolerance). This dual effect explains their vital role in cancer development and progression. DCs have been tested as a predictor of outcomes for cancer progression. Eight studies evaluated tumour-infiltrating DCs (TIDCs) as a predictor for colorectal cancer (CRC) outcomes. The detection of TIDCs has not kept pace with the increased knowledge about the identification of DC subsets and their maturation status. For that reason, it is difficult to draw a conclusion about the performance of DCs as a predictor of outcome for CRC. In this review, we comprehensively examine the evidence for the in situ immune response due to DC infiltration, in predicting outcome in primary CRC and how such information may be incorporated into routine clinical assessment.